Diffusion-weighted magnetic resonance imaging in the early detection of tumourresponse to therapy - Dodd, Nick J.F. (Radiology and oncology (Ljubljana), 1998)
Early detection of the effects of therapy offers distinct clinical advantages for the management of the patient, since the response of a tumour to a particular therapy may vary considerably from patient to patient. A pre-clinical tumour model was used to study the effects of two novel therapies, photodynamic therapy and electrotherapy, in addition to a well established modality, radiotherapy. In each case, diffusion-weighted magnetic resonance imaging was found to be of value in determining the therapeutic response, within two days of treatment. Following photodynamic therapy, the apparent diffusion coefficient (ADC) of water in those regions of the tumour that became necrotic showed a marked increase within one day of treatment, while no significant increase was detectable in those regions that remained viable. A similar increase in ADC was observed following electrotherapy, whether anodic or cathodic, the increase being detected within minutes of treatment in the regions of primary damage and within about one day in the regions of secondary ischaemic nercrosis. The changes produced by radiotherapywere less marked than those produced by the other therapies, but, following doses that produce a high proportion of killing, there was a statistically significant increase in ADC within one or two days of treatment.
Keywords: Electric stimulation therapy; Magnetic resonance angiography; Mice; Neoplasms, experimental; Phototherapy; Radiotherapy; Therapy